Androgen receptor signaling pathways as a target for breast cancer treatment. Issue 10 (October 2016) - Pietri, Elisabetta; Conteduca, Vincenza; Andreis, Daniele; Massa, Ilaria; Melegari, Elisabetta; Sarti, Samanta; Cecconetto, Lorenzo; Schirone, Alessio; Bravaccini, Sara; Serra, Patrizia; Fedeli, Anna; Maltoni, Roberta; et al.
Abstract : The androgen receptor (AR) is a ligand-dependent transcription factor, and its effects on breast range from physiological pubertal development and age-related modifications to cancer onset and proliferation. The prevalence of AR in early breast cancer is around 60%, and AR is more frequently expressed in ER-positive than in ER-negative tumors. We offer an overview of AR signaling pathways in different breast cancer subtypes, providing evidence that its oncogenic role is likely to be different in distinct biological and clinical scenarios. In particular, in ER-positive breast cancer, AR signaling often antagonizes the growth stimulatory effect of ER signaling; in triple-negative breast cancer (TNBC), AR seems to drive tumor progression (at least in luminal AR subtype of TNBC with a gene expression profile mimicking luminal subtypes despite being negative to ER and enriched in AR expression); in HER2-positive breast cancer, in the absence of ER expression, AR signaling has a proliferative role. These data represent the rationale for AR-targeting treatment as a potentially new target therapy in breast cancer subset using androgen agonists in some AR-positive/ER-positive tumors, AR antagonists in triple-negative/AR-positive tumors and in combination with anti-HER2 agents or with other signaling pathways inhibitors (including PI3K/MYC/ERK) in HER2-positive/AR-positive tumors. Only the ongoing and future prospective clinical trials will allow us to establish which agents are the best option in every specific condition, keeping in mind that there is evidence of opposite androgens and AR agonist/antagonist drug effects on cell proliferation particularly in AR-positive/ER-positive tumors.